"Whatever you do, do not let a boy grow up without Latin": a comparative study of nineteenth-century Latin textbooks in English and Prussian education - Kirk, Sonya (2016)
Considering textbooks as cultural artefacts that both reflect prevailing paradigms and construct knowledge (Issitt 2004; Apple 2004), this research compares nineteenth-century Latin textbooks intended for pupils in England with those intended for pupils in Prussia in the light of their differing educational, linguistic and social contexts. This dissertation fills a gap in Anglo-German historiography for the nineteenth century from three intertwined perspectives: cultural history, the history of education and the history of linguistic ideas, by investigating how textbook authors treated Latin grammar in the light of cultural ideologies (including the role of Classics in elite education, education for empire) and developments in pedagogy and philology, at a time when formal education was just becoming established, and when curriculum design, educational administration, and educational philosophy in England were all heavily influenced by German scholarship. Using a corpus of 100 Latin textbooks used in nineteenth-century England and Prussia, textbook content was examined both quantitatively and qualitatively. The results show that nineteenth-century Latin textbooks intended for pupils in England and Prussia conveyed different cultural information to their respective audiences. Challenging popular belief, pedagogical findings from this research demonstrate that Latin textbooks included a range of innovative teaching methods and techniques. As Latin is a ‘dead’ language, it is commonly perceived to be linguistically static, but by analysing the linguistic presentation of the Latin language in nineteenth-century textbooks, we find that some of the most basic linguistic components of Latin, such as the alphabet and the noun case system, were reconsidered and altered. This research shows that, though foreign language textbooks are under-studied, they offer insight into cultural history, the history of teaching and learning and the history of linguistic ideas which can be found in no other source and, ultimately, contextualise the current state of foreign language teaching.